Novel treatment strategy targeting interleukin-6 induced by cancer associated fibroblasts for peritoneal metastasis of gastric cancer - Ema Mitsui; Satoru Kikuchi; Tomohiro Okura; Hiroshi Tazawa; Yuta Une; Noriyuki Nishiwaki; Shinji Kuroda; Kazuhiro Noma; Shunsuke Kagawa; Toshiaki Ohara; Junko Ohtsuka; Rieko Ohki; et al. (Scientific Reports)
Abstract Cancer-associated fibroblasts (CAFs) are a crucial component in the tumor microenvironment (TME) of peritoneal metastasis (PM), where they contribute to tumor progression and metastasis via secretion of interleukin-6 (IL-6). Here, we investigated the role of IL-6 in PM of gastric cancer (GC) and assessed whether anti-IL-6 receptor antibody (anti-IL-6R Ab) could inhibit PM of GC. We conducted immunohistochemical analysis of IL-6 and α-smooth muscle (α-SMA) expressions in clinical samples of GC and PM, and investigated the interactions between CAFs and GC cells in vitro. Anti-tumor effects of anti-IL-6R Ab on PM of GC were investigated in an orthotopic murine PM model. IL-6 expression was significantly correlated with α-SMA expression in clinical samples of GC, and higher IL-6 expression in the primary tumor was associated with poor prognosis of GC. Higher IL-6 and α-SMA expressions were also observed in PM of GC. In vitro, differentiation of fibroblasts into CAFs and chemoresistance were observed in GC cells cocultured with fibroblasts. Anti-IL-6R Ab inhibited the progression of PM in GC cells cocultured with fibroblasts in the orthotopic mouse model but could not inhibit the progression of PM consisting of GC cells alone. IL-6 expression in the TME was associated with poor prognosis of GC, and CAFs were associated with establishment and progression of PM via IL-6. Anti-IL-6R Ab could inhibit PM of GC by the blockade of IL-6 secreted by CAFs, which suggests its therapeutic potential for PM of GC.